Combating Corruption in Procurement: The Synergy of Law Enforcement, Civil Society, and Digital Oversight - Baskoro, Aji (Ikatan Ahli Pengadaan Indonesia (IAPI), 2025)
Corruption in procurement remains a critical challenge that undermines economic development, distorts market competition, and erodes public trust in governance. While conventional legal frameworks and enforcement mechanisms have played a crucial role in addressing this issue, emerging digital oversight technologies and civil society engagement offer new opportunities to enhance transparency and accountability. This study adopts a normative juridical research methodology, integrating a statutory approach, conceptual approach, and comparative approach to examine the mechanisms for combating corruption in public procurement. The statutory approach assesses the legal framework governing procurement oversight in Indonesia, particularly Presidential Regulation No. 16 of 2018 and regulations issued by the National Public Procurement Agency (LKPP). The conceptual approach explores governance theories, including good governance, public participation, and e-governance, to evaluate institutional oversight, civil society involvement, and digital interventions. Furthermore, the comparative approach examines procurement oversight models from South Korea, identifying best practices for institutional coordination, regulatory enforcement, and technological integration. The findings reveal that digital tools, such as e-procurement systems, public reporting platforms, and real-time monitoring technologies, significantly reduce corruption risks by enhancing transparency and minimizing human discretion. Additionally, civil society organizations play a vital role in ensuring policy effectiveness and fostering public participation in procurement oversight. However, challenges remain, including legal loopholes, resistance from vested interests, and the adaptability of corrupt actors to technological advancements. This study highlights the necessity of an integrated approach that combines legal reform, civic engagement, and digital innovation to create a more accountable and corruption-resistant procurement system. Keywords: Procurement Corruption, Law Enforcement, Civil Society, Digital Oversight, Transparency